Waqf: Opportunities, challenges, and way forward - Abdullah, Moha Asri (2020)
Waqf play crucial role in economic growth and economic development in Muslim countries. Waqf can contribute hugely to income generation, income distribution, the provision of infrastructure amenities and social facilities. Moreover, Waqf can also be an avenue for employment and poverty eradication, provision of good health and education.